2008
DOI: 10.1093/annonc/mdm474
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase II study of cetuximab plus cisplatin/vinorelbine compared with cisplatin/vinorelbine alone as first-line therapy in EGFR-expressing advanced non-small-cell lung cancer

Abstract: Background: The Lung Cancer Cetuximab Study is an open-label, randomized phase II pilot study of cisplatin and vinorelbine combined with the epidermal growth factor receptor (EGFR)-targeted monoclonal antibody cetuximab versus cisplatin and vinorelbine alone, in patients with advanced EGFR-expressing, non-small-cell lung cancer (NSCLC). End points of the study are activity, safety and pharmacokinetics. Results: Eighty-six patients were randomly allocated to the study (43 per arm). Confirmed response rates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
150
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(154 citation statements)
references
References 32 publications
4
150
0
Order By: Relevance
“…Over the past decade, the EGFR has been primary focus for biologically targeted therapies, with the most active treatments being monoclonal antibodies. Cetuximab is an FDA approved MoAb agent for use in advance or metastatic disease and exhibit efficacy in NSCLC and metastatic colorectal cancer (mCRC) (Butts et al, 2007;Rosell et al, 2008;Van Cutsem et al, 2009). However, No significant increase of OS was observed for panitumumab-FOLFOX4 versus FOLFOX4 in mCRC (median OS, 23.9 v 19.7 months, respectively; HR, 0.83; 95% CI, 0.67 to 1.02; P=.072) (Douillard et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, the EGFR has been primary focus for biologically targeted therapies, with the most active treatments being monoclonal antibodies. Cetuximab is an FDA approved MoAb agent for use in advance or metastatic disease and exhibit efficacy in NSCLC and metastatic colorectal cancer (mCRC) (Butts et al, 2007;Rosell et al, 2008;Van Cutsem et al, 2009). However, No significant increase of OS was observed for panitumumab-FOLFOX4 versus FOLFOX4 in mCRC (median OS, 23.9 v 19.7 months, respectively; HR, 0.83; 95% CI, 0.67 to 1.02; P=.072) (Douillard et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of cisplatin plus vinorelbine with and without cetuximab in the first-line setting was first assessed within a phase II randomized trial [22], and then in a larger phase III study, the First-Line trial for patients with EGFREXpressing advanced NSCLC (FLEX) [23]. In total, 1,125 chemotherapy-naïve EGFR ϩ patients enrolled in the FLEX trial were randomized to either chemotherapy plus cetuximab or chemotherapy alone.…”
Section: Advanced Diseasementioning
confidence: 99%
“…73 The US (BMS-099) 74 trial looked at unselected patients with NSCLC to taxane plus cetuximab, and reached its primary endpoint of enhanced median OS (9.7 versus 8.4 months) but not PFS. A review by Pirker et al (FLEX 71 , BMS 099 74 , BMS 100 75 , LUCAS 76 [see Table 4]) confirmed the consistent benefit of adding cetuximab to chemotherapy in patients with advanced NSCLC of all histological subtypes in terms of OS (P <0.01), PFS (P <0.03), and OS rate (OR 1.463, P <0.001). 77 The Southwest Oncology Group trial is a phase II study that combined cetuximab to carboplatin, paclitaxel and bevacizumab for 6 cycles, followed by bevacizumab weekly until disease progression.…”
Section: Vascular Targets and Bevacizumab (Monoclonal Antibody Targetmentioning
confidence: 94%